The portrayal of main female characters from across country using the postcolonial feminism approach :a study on four novels from India, Malaysia, Nigeria, and Singapore - Marie Albina, Ho Pei Pei. (Universiti Malaysia Sarawak (UNIMAS), 2008)
This study aims to find out the portrayal of main female characters in novels by female authors from postcolonial countries, in which the foci are on the placement of women in her culture and society, the strength to rise as a woman, and the influence of double colonization upon these women. The texts used are; (i)Joss and Gold by Shirley Lim, (ii)Following the Wrong God Home by Catherine Lim, (iii) Arranged Marriages by Chitra Banerjee Divakaruni, and (iv)The Joys of Motherhood by Buchi Emecheta. Data collection is done through textual analysis using the postcolonial feminism theoretical framework. The results of this study shows distinctive cultural bondage exists and determines the placement of women in her society. Besides that, the emergence of female figures is prominent due to circumstances these women encountered. However, double colonization occurs and is inevitable amongstb postcolonial women. The findings of this study bridge the existing knowledge gap noted from related previous studies.